Epidemiological analysis on children and adolescents with COVID-19 in a central area of Calabria region: one year of pandemia - Talarico, Valentina; Roppa, Katia; Alcaro, Teresa; Vinci, Maria; Minchella, Pasquale; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
not available